Executive Risk in Indonesia's State-Owned Enterprises: A Juridical and Governance Analysis - Bagus Satrio Utomo Prawiraharjo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This paper presents a juridical and governance analysis of executive risk aversion in Indonesia’s State-Owned Enterprises (SOEs/BUMN). Despite their strategic economic role, qualified professionals increasingly decline BUMN executive positions due to systemic legal ambiguities and governance weaknesses. The study identifies a core tension between the Business Judgment Rule (BJR), which protects good-faith corporate decisions under Law No. 40 of 2007, and the expansive interpretation of “State Financial Loss” under anti-corruption statutes, which criminalizes ordinary business losses. Through doctrinal analysis and the case study of former Pertamina CEO Karen Agustiawan, the paper demonstrates how this legal dualism fosters a chilling effect on strategic leadership. It further examines how political patronage undermines merit-based talent management, rendering BUMN governance unattractive to qualified professionals. The analysis evaluates Indonesia’s 2025 BUMN reforms, including Law No. 1 of 2025, the dissolution of the Ministry of SOEs, and the creation of the Danantara holding agency, as a legislative effort to de-risk executive roles by clarifying asset status, strengthening BJR protections, and depoliticizing oversight. The paper concludes that while these reforms are structurally promising, their efficacy hinges on institutional buy-in from law enforcement and the judiciary, and recommends judicial guidance, depoliticized appointments, and talent mobility to restore confidence in BUMN leadership.